Fibrin Sealants Do Not Reduce the Rate of Seroma Formation in Postmastectomy Breast Reconstruction: A Systematic Review and Meta-analysis - Massada, Karen E. M.; Wu, Meagan; Webster, Theresa K.; Panichella, Juliet; Coronado, Michael C.; Talemal, Lindsay; Elmer, Nicholas; Araya, Sthefano; Brebion, Rohan; Baltodano, Pablo A.; Patel, Sameer A. (Journal of Reconstructive Microsurgery Open, 2022)
Background Breast reconstruction using deep inferior epigastric perforator (DIEP) and latissimus dorsi (LD) flaps following mastectomy are associated with seroma formation, most commonly at the donor site. We sought to perform an updated systematic review and meta-analysis on the effects of fibrin sealant on donor-site complications following DIEP and LD flap breast reconstruction.Methods A comprehensive literature search was conducted (March 2021) in PubMed, OVID, and Cochrane databases. Articles analyzing the efficacy of fibrin glue in reducing donor-site morbidity in DIEP and LD breast reconstruction were included. The outcomes assessed were seroma formation and duration of drainage.Results A total of 17,265 articles were screened, and 9 articles were selected for analysis, which comprised 632 surgical sites in 611 patients. Comparing fibrin glue and quilting to quilting alone showed no significant difference in seroma formation (pooled risk ratio [RR]: 0.51; 95% confidence interval [CI]: 0.12, 2.25). Similarly, comparing fibrin glue alone to no fibrin glue showed no significant difference in seroma formation (pooled RR: 1.03; 95% CI: 0.66, 1.61) or duration of drain (pooled RR: −0.85; 95% CI: −4.09, 2.40); there was however a difference in duration of drain in those who received fibrin glue and quilting versus quilting alone (pooled RR: −2.13; 95% CI: −3.27, −0.99).Conclusion The existing literature supports that the use of fibrin glue is not associated with a decrease in seroma formation in DIEP and LD flaps and is weakly associated with a reduction in the drainage duration only if used in conjunction with quilting.
Keywords: fibrin glue; fibrin sealant; seroma rate; drain duration; breast reconstruction; deep inferior epigastric perforator flap; DIEP flap; latissimus dorsi flap; LD flap; donor site